1993
DOI: 10.1002/kin.550250703
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the BrO + NO2 association reaction. Temperature and pressure dependence in the falloff regime

Abstract: A laser flash photolysis-long path absorption technique has been employed to study the kinetics of the reaction BrO + NO2 + M Q products as a function of temperature (248-346 K), pressure (16-800 torr), and buffer gas identity (N2, CF4). The reaction is found to be in the falloff regime between third and second-order over the entire range of conditions investigated. This is the first study where temperature-dependent measurements of kl ( P , T ) have been reported at pressures greater than 12 torr; hence, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
1
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 20 publications
0
27
1
1
Order By: Relevance
“…Although gas-phase halogen chemistry in the Arctic has now been studied for several decades (Impey et al, 1997;Hausmann and Platt, 1994;Barrie et al, 1988), few studies have examined the effect of atmospheric NO x on these halogen chemical cycles. Model studies have shown that NO x can react with halogen radicals through several reactions (as shown in Reactions R8-R12), to produce inorganic halogen nitrates or nitryl halides, which can, in turn, activate further halogen chemistry through heterogeneous reactions (Cao et al, 2014;Toyota et al, 2013;Morin et al, 2007Morin et al, , 2012Thomas et al, 2012;Evans et al, 2003;Rossi, 1999, 2002;von Glasow et al, 2002;Thorn et al, 1993), and thereby alter gas phase halogen radical reaction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Although gas-phase halogen chemistry in the Arctic has now been studied for several decades (Impey et al, 1997;Hausmann and Platt, 1994;Barrie et al, 1988), few studies have examined the effect of atmospheric NO x on these halogen chemical cycles. Model studies have shown that NO x can react with halogen radicals through several reactions (as shown in Reactions R8-R12), to produce inorganic halogen nitrates or nitryl halides, which can, in turn, activate further halogen chemistry through heterogeneous reactions (Cao et al, 2014;Toyota et al, 2013;Morin et al, 2007Morin et al, , 2012Thomas et al, 2012;Evans et al, 2003;Rossi, 1999, 2002;von Glasow et al, 2002;Thorn et al, 1993), and thereby alter gas phase halogen radical reaction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…BrO + NO 2 f BrONO 2 (7) BrONO 2 + hν f Br + NO 3 (8) NO 3 + hν f NO + O 2 (9) NO + O 3 f NO 2 + O 2 (10) net: 2O 3 f 3O 2…”
Section: Introductionunclassified
“…Because BrONO2 has a relatively short lifetime, the BrONO2 concentration responds very rapidly to any change in NO2, as occurs, for example, due to denoxification on surfaces. The rate recommended for the formation of BrONO2 by DeMote et al[1992] is based on kinetic measurements made byThorn et al [1993] andDanis et al [1990]. These measurements were made at over 260 K and so quite large temperature extrapolations are involved when considering lower stratospheric temperatures.…”
mentioning
confidence: 99%